(3GdNQhL ef GdeCRb (B:s (3af EOGQI GdCReGJ (B/s - (3aJMj, eMeO,s 1910-1986 ((3GdbGgQI (B:s (3OGQ GdJhRjY hGdfTQ GdESdGejI,s, 2001)
(3jJfGhd GdcJGH Yf GdCReI heGgjJgG heaghegG hGdJNWjW GdfGLM ddJYGed eY GdCReI(B.s
(3HHdjhLQGajI (B: (3U(B. 331.s
Keywords: (3EOGQI GdCReGJs; (3EOGQI GdCYeGds